STRUKTUR TEKS EKSPLANASI DALAM BUKU BAHASA INDONESIA KELAS VIII TERBITAN KEMENDIKBUD EDISI REVISI 2017 - Nadia Vitaloka; Akhyaruddin Akhyaruddin; Andiopenta Purba (Universitas Negeri Makassar, 2024)
The purpose of this study is to describe the linguistic structure of the explanatory text in the Indonesian language book for Class VIII published by the Ministry of Education and Culture Revised Edition 2017. This research is a qualitative descriptive research. This research data is in the form of descriptions of words, sentences and paragraphs narrated after an in-depth analysis process. The data collection techniques were literature study and documentation study. In this study, the researcher used data analysis with stages, namely data reduction, data presentation, and conclusion. The results showed that the explanatory texts of Prince Diponegoro, Development of Bandung Regency, Energy Flow, and Fossil Formation completely fulfilled the three parts of the explanatory text structure consisting of general statements, sequence of events and reviews.